Placebo response in psoriatic arthritis clinical trials: a systematic review and meta-analysis. (19th October 2021) - Erre, Gian Luca; Mavridis, Dimitris; Woodman, Richard John; Mangoni, Arduino Aleksander
Abstract: Objective: To determine the placebo response rate in PsA randomized clinical trials (RCTs), its contributing factors and impact on the effect size of active treatments. Methods: We searched multiple databases, from inception to 20 December 2020, for placebo-controlled RCTs in PsA. We used a random-effects meta-analysis to pool the response rates for the ACR20 criteria in the placebo arm, determined the risk difference for treatment vs placebo, and used meta-regression to determine the factors associated with placebo response rates. The risk of bias was assessed in duplicate. The study protocol was registered with PROSPERO: CRD42021226000. Results: We included 42 RCTs (5050 patients receiving placebo) published between 2000 and 2020. The risk of bias was low in 28 trials, high in four, and with some concerns in 10. The pooled placebo response rate was 20.3% (95% CI: 18.6%, 22.1%; predicted intervals, 11.7–29.0%), with significant between-trial heterogeneity ( I 2 = 56.8%, P < 0.005). The pooled risk difference for treatment vs placebo was 27% (95% CI: 24%, 31%). In the multivariable meta-regression, there was a 15% (95% CI: 2.9%, 29.8%) increase in the odds of achieving the placebo response for each 5-year increment in publication year ( P = 0.016). In addition, the active treatment risk difference decreased for every 5-year increment in publication year (β = −0.053, 95% CI: −0.099, −0.007; P = 0.024) but was not associated with the placebo response. Conclusion: Despite increasing over time, the placebo response for ACR20 in PsA RCTs was not associated with the active treatment effect size.